Liquidity, Trading Activity, and Stock Price Volatility: Evidence from a Stressed Market - Mupondo, Ndava Constantine (Finance & Economics Review, 2022)
Purpose: While the bulk of previous research focused on security-level volatility and the relationship of its determinants, the current study considers the relationship between the number of trades, lagged absolute returns, trading volume, bid-ask spread, and price volatility on the Zimbabwe stock market. Methods: The study applied Hausman's (1982) tests of the specification. The parameters and elasticity of explanatory variables have been estimated by utilizing the Generalized Method of Moments (GMM) procedure in a five-equation structural model. The data were obtained from a web-based financial market platform, Investing.com for the period between 2009 and 2021. Results: Results show that inflation had a positive relationship with stock price volatility, which provided a hedge against inflation. There exists an indistinguishable difference between the random effects (RE) and fixed effects (FE) results and those obtained using the Pooled Ordinary Least Squares (POLS) on the total sample reflecting a cohesion of these findings. Implications: Understanding the relationship between inflation and market risk (volatility) can be beneficial to the investor in selecting the appropriate and most convenient investment strategy. From a policy-making perspective, strategic policy measures employed towards reducing inflation would certainly reduce stock market volatility and boost investor confidence.